Butylated hydroxytoluene (BHT) emitted by fungi naturally occurring in olives during their pre‐processing storage for improving olive oil stability. Issue 11 (17th July 2017) - Gharbi, Ines; Issaoui, Manel; El Gharbi, Sinda; Gazzeh, Nour‐Eddine; Tekeya, Meriem; Mechri, Beligh; Flamini, Guido; Hammami, Mohamed
Abstract : Extra virgin olive oil is widely consumed because of its nutritional benefits and sensory properties which are very important to be preserved in the product. Therefore, chemically synthesised compounds, such as butylated hydroxyanisole (BHA) and butylated hydroxytoluene (BHT), are widely used as antioxidants in oil products. It is well known that the activity of some micro‐organisms able to oxidise free fatty acids can lead to the loss of the stability of the final product. Nevertheless, several researchers have been recently motivated to evaluate the potential of micro‐organisms on the production of bioactive compounds. In this paper, headspace solid micro‐extraction (HS‐SPME) and gas chromatography‐mass spectrometry (GC‐MS) were used for the characterization and investigation of Fungal Organic Volatile Metabolites (FOVCs) emitted by 14 fungal strains isolated from olives during their pre‐processing storage. A wide range of volatile compounds were detected among them, BHT was produced at levels ranging between 0.3 and 13.1%. This compound could be considered for the industry as natural antioxidant to substitute the synthetic ones used for ameliorating the stability of olive oil and other fatty food products. Practical applications: As the pre‐processing storage step is inevitable for several practical reasons, inducing the outgrowth of olive microflora (mainly fungi), which critically affect the physiological state of the fruit and thus the quality of the correspondent oil, this paper try to elucidate the potential of these naturally developing strains and their metabolites (FVOCs) of producing bioactive compounds mainly the BHT which could be considered by the industry in order to substitute the synthetic one largely used to improve the stability of olive oil and other food products. Volatiles, when coupled with the power "omics" technologies represent a new frontier in bio‐prospecting. FOVCs profile of 14 fungi strains isolated from olives stored during 2, 5, and 7 days in plastic bags is determinate by HS‐SPME‐GC‐MS. 87 FVOCs are detected representing six groups dominated by the non‐terpene derivatives. Interestingly, a compound with particular interest is detected; the Butylated Hydroxytoluene (BHT) is naturally emitted by 11 strains from the 14 isolated fungi at levels ranging between 0.3 and 13.1% (for Aspergillus conicus ). A result which could be considered by the industry in order to substitute the synthetic antioxidants largely used to improve the stability of olive oil and other food products. Abstract : FOVCs profile of 14 fungi strains isolated from olives stored during 2, 5, and 7 days in plastic bags is determinate by HS‐SPME‐GC‐MS. 87 FVOCs are detected representing six groups dominated by the non‐terpene derivatives. Interestingly, a compound with particular interest is detected; the Butylated Hydroxytoluene (BHT) is naturally emitted by 11 strains from the 14 isolated fungi at levels ranging between 0.3 and 13.1% (for Aspergillus conicus ). A result which could be considered by the industry in order to substitute the synthetic antioxidants largely used to improve the stability of olive oil and other food products.